Investigation of Known Genetic Mutations of Arabian Horses in Egyptian Arabian Foals with Juvenile Idiopathic Epilepsy. (24th November 2017) - Aleman, M.; Finno, C.J.; Weich, K.; Penedo, M.C.T.
Abstract : Background: The carrier status of lavender foal syndrome (LFS), cerebellar abiotrophy (CA), severe combined immunodeficiency (SCID), and occipitoatlantoaxial malformation (OAAM1) in foals with juvenile idiopathic epilepsy (JIE) is unknown. Hypothesis/Objectives: To determine the carrier status of LFS, CA, SCID, and OAAM1 in foals with JIE. Animals: Ten foals with JIE. Materials and Methods: Archived DNA samples were tested for known genetic mutations causing LFS, CA, SCID, and OAAM1. The inclusion criteria consisted of having been diagnosed with JIE by ruling out other causes of seizures in foals and supported by electroencephalographic examination. Results: Ten Egyptian Arabian horses (5 females and 5 males) were phenotyped as foals with JIE by electroencephalography (EEG). All foals were negative for the genetic mutations that cause LFS, CA, SCID, and OAAM1 except for 1 foal that was a carrier of CA. Conclusions and Clinical Importance: Juvenile idiopathic epilepsy of Egyptian Arabian foals and LFS appear to be phenotypically and genetically distinct disorders. There was no apparent association between JIE and LFS, CA, SCID, and OAAM1.